Degradation of lignin by Bacillus altitudinis SL7 isolated from pulp and paper mill effluent. (2nd December 2021) - Khan, Sanam Islam; Zarin, Asaf; Ahmed, Safia; Hasan, Fariha; Belduz, Ali Osman; Çanakçi, Sabriye; Khan, Samiullah; Badshah, Malik; Farman, Muhammad; Shah, Aamer Ali
Abstract: Lignin is a major by-product of pulp and paper industries, and is resistant to depolymerization due to its heterogeneous structure. Degradation of lignin can be achieved by the use of potential lignin-degrading bacteria. The current study was designed to evaluate the degradation efficiency of newly isolated Bacillus altitudinis SL7 from pulp and paper mill effluent. The degradation efficiency of B. altitudinis SL7 was determined by color reduction, lignin content, and ligninolytic activity from degradation medium supplemented with alkali lignin (3 g/L). B. altitudinis SL7 reduced color and lignin content by 26 and 44%, respectively, on the 5th day of incubation, as evident from the maximum laccase activity. Optimum degradation was observed at 40 °C and pH 8.0. FT-IR spectroscopy and GC-MS analysis confirmed lignin degradation by emergence of the new peaks and identification of low-molecular-weight compounds in treated samples. The identified compounds such as vanillin, 2-methyoxyhenol, 3-methyl phenol, oxalic acid and ferulic acid suggested the degradation of coniferyl and sinapyl groups of lignin. Degradation efficiency of B. altitudinis SL7 towards high lignin concentration under alkaline pH indicated the potential application of this isolate in biological treatment of the lignin-containing effluents. HIGHLIGHTS: Bacillus altitudinis SL7 isolated from effluent could efficiently degrade lignin under alkaline conditions. Degradation efficiency was determined by analyzing lignin content, color reduction, and ligninolytic enzyme activity. Extracellular laccase from B. altitudinis SL7 can play a significant role in the depolymerization of lignin. Various low-molecular-weight lignin degradation products were determined through GC-MS.